Primary orbital melanoma: A report of a case and comprehensive review of the literature. (2nd November 2021) - Adetunji, Modupe O.; McGeehan, Brendan; Lee, Vivian; Maguire, Maureen G.; Briceño, César A.
ABSTRACT: Purpose: To review the clinical features and treatment-associated outcomes of primary orbital melanoma among cases reported in the literature and to present a case treated with orbital exenteration and post-operative radiotherapy. Methods: Case reports and case series on primary orbital melanoma published in the literature between 1980 and 2020 were reviewed. Data collected included patient demographics, presenting ocular symptoms, diagnostic imaging, histology, management, and outcomes. Results: Eighty-eight cases of primary orbital melanoma were reviewed. The average age at presentation was 45 years and 58% of patients were male. The most common presenting symptoms and signs were proptosis (73%), decreased visual acuity (32%), pain (14%), diplopia (15%), and palpable mass (9%). Imaging frequently showed a well-circumscribed enhancing lesion. Diagnosis was made by histology in all cases, and orbital blue nevus was identified in 42%. In the majority of cases, treatment consisted of orbital exenteration (54%) or excision (38%). Adjuvant radiotherapy was given in 47% of cases. For the 72 patients with reported outcomes, 36% had metastases, 15% had local recurrence, and 32% died of metastatic disease. Patients who received surgery and radiotherapy had improved survival compared to those who received surgery alone ( p = .01). There was no difference in survival between those who underwent orbital exenteration or excision ( p = .16). Conclusions: Primary orbital melanoma is a rare malignancy and should be considered in patients with a history of unilateral proptosis and a well-defined orbital mass on imaging. Surgery remains the mainstay of treatment. Adjuvant radiotherapy may improve patient survival.